Design of New Antidiabetic Compounds Using Structure-Based Drug Design Method on Kaempferol Derivatives from Guava Leaves (Psidium guajava L.) - Nadine Aurelia Hasugian; Tiara Ajeng Litsyani; Danang Raharjo (International Journal of Health Engineering and Technology, 2026)
Diabetes mellitus is a chronic metabolic disorder with increasing global prevalence, requiring new antidiabetic candidates to inhibit α-amylase and α-glucosidase enzymes to control postprandial glucose. This study aims to design kaempferol derivative compounds from guava leaves (Psidium guajava L.) through Structure-Based Drug Design in silico. This type of computational experimental study uses 15 ligands as purposive samples from the population of flavonoid compounds and target enzymes. Instruments include ChemDraw, PyRx-AutoDock Vina, Swiss ADME, Toxtree, and Discovery Studio, with analysis of binding free energy (ΔG), RMSD, and ADME-toxicity prediction. The results showed that the new compound 4-(2-hydroxy-1-(hydroxymethoxy butyl)cyclohexan-1-ol has a ΔG of -5.5 kcal/mol (α-amylase) and -5.9 kcal/mol (α-glucosidase), RMSD <2 Å, fulfills Lipinski's rule, and has low toxicity (Low Class I). The conclusion states that this compound has the potential as a safe antidiabetic candidate with implications for the development of local flavonoid-based drugs